2021
DOI: 10.3390/wevj12010004
|View full text |Cite
|
Sign up to set email alerts
|

Dual Battery Control System of Lead Acid and Lithium Ferro Phosphate with Switching Technique

Abstract: The increase in electric vehicles needs to be supported by the existence of reliable energy storage devices. The battery, as an energy storage system, has its advantages and disadvantages. The combination of different battery types is chosen since the battery is one of the energy storage systems with mature technology and low life cycle cost. A solution that can be proposed to cover the weakness of each battery is the use of the Dual Battery System (DBS). In this project, a dual battery control system with a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…FOPID shows superior performance as compared to fuzzy logic control during HEV operation. On the other hand, [29] proposes a double switching-based control for a combination of LAB and LIB energy storage systems for EVs to explore the batteries' pros and cons. This control selects the battery to be used during different vehicle operation modes under specified conditions and limits.…”
Section: State-of-the-art Literature Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…FOPID shows superior performance as compared to fuzzy logic control during HEV operation. On the other hand, [29] proposes a double switching-based control for a combination of LAB and LIB energy storage systems for EVs to explore the batteries' pros and cons. This control selects the battery to be used during different vehicle operation modes under specified conditions and limits.…”
Section: State-of-the-art Literature Analysismentioning
confidence: 99%
“…The integrated solution ensures that the batteries operate within their desired limits. A contribution that enhances the performance in [29], in which the study assessed the system in terms of improving vehicle range only.…”
mentioning
confidence: 99%
“…Numerous studies have been carried out focusing on the combination of two batteries [9][10][11][12]. A HESS composed of a lead-acid (LA) battery as the energy source and a Li-ion battery as the power source was proposed [9] to power a light EV.…”
Section: Introductionmentioning
confidence: 99%
“…It was concluded that the combination of the two batteries results in storage systems lighter than those using Li-ion batteries alone. Finally, in [12], the hybridization of an LA battery and a Li-ion battery was compared to the individual use of each battery in a hybrid vehicle. The results show that the use of a DBSS can lead to energy savings of up to 68.6% in the LA battery and up to 29.5% in the Li-ion battery, thereby prolonging the range of the vehicle.…”
Section: Introductionmentioning
confidence: 99%
“…In that work, the measured current was between 0.002 and 0.05 mA, associated with a little amount of visible noise in the readings. Muhammad Nizam et al [8] described the usage of an ACS712 current sensor module in monitoring battery consumption. According to the research findings, the precision and accuracy of the current sensor were 64.91% and 83.75%, respectively.…”
Section: Introductionmentioning
confidence: 99%